Multiple regression analysis of some bottom soil properties on the growth of benthos in nursery ponds - Habib, M Ashan Bin; Haque, Imdadul; Ali, M Mohsin (Indian Journal of Fisheries, 2011)
The benthos are most important organisms of natural water bodies which are directly or indirectly used as food and energy for fishes and other organisms. Various physico-chemical properties of bottom soil have combined effect on the growth of benthos. Variations in production of benthos in different ponds at different depths and in different months may be due to differential fertility and ecological conditions p-evailing in those habitats. The work on depthwise. monthwise and pondwise variations of benthos, the combined effect of bottom soil properties on the benthos, their interactions and intrarelations based on statistical analyses, are very rare (Ahmed et al. 1987, Habib et al. 1987). To analyse some of these aspects, the present work was undertaken